PEEK-based self-lubricating composite material part and forming method thereof
Patent Information
- Application Number
- CN202311634007.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-11-30
AI Technical Summary
[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种PEEK基自润滑复合材料制件及其成形方法,以解决现有技术PEEK材料摩擦学性能不高以及无法实现表面/微观一体化成形的技术问题
[0021] The molding method for PEEK-based self-lubricating composite parts disclosed in this invention uses boron nitride and polytetrafluoroethylene (PTFE) as reinforcing materials. One advantage lies in the material selection, primarily including: 1) Boron nitride is an excellent solid lubricant, especially h-BN. Its atomic layers are connected by weak van der Waals forces, making hexagonal boron nitride easily shear to form slip surfaces, significantly reducing the coefficient of friction. The addition of h-BN also improves the wear resistance of the composite material. h-BN has excellent thermal stability, allowing PEEK to maintain its lubricating properties in high-temperature environments. h-BN can enhance the thermal conductivity of PEEK, facilitating rapid heat transfer; 2) Polytetrafluoroethylene (PTFE) has good dispersibility, further reducing the coefficient of friction and providing continuous lubrication, also contributing to improved wear resistance of PEEK. PTFE can reduce adhesion between PEEK and other materials; 3) The combination of h-BN and PTFE can produce a synergistic effect, forming a more uniform and powerful lubricating layer, further improving the self-lubricating performance of PEEK. Due to the thermal stability of h-BN and PTFE, PEEK can operate over a wider temperature range. In addition to lubrication properties, the addition of h-BN and PTFE effectively reduces warpage during laser powder bed melting, improving the mechanical properties of PEEK-based composites.
Smart Images

Figure CN117601421B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of additive manufacturing technology, specifically relating to a PEEK-based self-lubricating composite material part and its forming method. Background Technology
[0002] Traditional lubrication methods, such as lubricating oils and greases, while effectively reducing friction and wear, may be unstable or unsuitable in certain applications, such as vacuum or high-temperature environments. Furthermore, the use of lubricants can lead to increased maintenance costs and environmental pollution. Therefore, under high-friction conditions, self-lubricating properties are crucial for material performance, as they can extend material lifespan, reduce energy loss, and improve the efficiency of mechanical systems. Self-lubricating properties refer to the ability of a material to automatically form a lubricating film and transfer film based on the tiny particles generated by its own wear during friction, without the need for additional lubricant, thus effectively reducing friction and wear.
[0003] Surface patterning technology can improve the self-lubricating properties of materials by designing microstructures on the material surface to accommodate and distribute lubricant. These microstructures can increase surface area, improve lubricant storage and release capacity, and thus improve frictional properties. This process typically begins with the design of the microstructure using computer-aided design tools to meet the specific requirements of the material. Then, an appropriate manufacturing method is selected, which can include machining, chemical etching, laser processing, etc., to apply the designed microstructure to the material surface. Surface patterning technology has wide applications in many fields, such as reducing friction, improving lubrication performance, and enhancing the properties of biomedical materials. Material selection is crucial for this technology because the material must possess sufficient strength and durability to support the microstructure and maintain its integrity during manufacturing. The application of this technology helps improve material properties and advances science and engineering. Laser powder bed melting (LPBF) is an important additive manufacturing technology that, through precise control of the laser beam, can achieve the integration of microstructures on or within the material surface, improving the performance of composite materials. It can manufacture complex-shaped parts without the need for a supporting structure, making LPBF a very flexible and efficient additive manufacturing technology. It can sinter polymer materials such as metals, ceramics, or PEEK powders, and has a wide range of applications in aerospace, automotive, electronics, medical, and consumer products.
[0004] Polyetheretherketone (PEEK) is a polymer with excellent properties such as thermal stability, biocompatibility, chemical resistance, mechanical strength, and low coefficient of friction, making it widely used in demanding engineering fields such as aerospace, medical devices, and the automotive industry. However, the performance of PEEK materials in high-friction and high-wear environments limits its application range. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a PEEK-based self-lubricating composite material part and its forming method, so as to solve the technical problems of low tribological properties of PEEK material and inability to achieve surface / microscopic integrated forming in the prior art.
[0006] To achieve the above objectives, the present invention employs the following technical solution:
[0007] This invention discloses a molding method for PEEK-based self-lubricating composite material parts, comprising:
[0008] PEEK, boron nitride and polytetrafluoroethylene were mixed to obtain PEEK-based self-lubricating composite powder;
[0009] A specific surface pattern structure is pre-designed in the CAD model, and computer-aided design software is used to make the size and distribution of the pattern meet specific application requirements to obtain the part model.
[0010] Based on the part model, PEEK-based self-lubricating composite powder was printed using LPBF macro-micro integrated printing technology to obtain PEEK-based self-lubricating composite parts with specific surface patterns.
[0011] Preferably, in the PEEK-based self-lubricating composite powder, PEEK accounts for 75% to 80% by mass, boron nitride accounts for 10% to 15%, and polytetrafluoroethylene accounts for 10% to 15%. During preparation, PEEK, boron nitride, and polytetrafluoroethylene are dried separately and then mixed. The drying temperature is 120 to 150°C, and the drying time is 600 to 720 minutes. A planetary stirrer is used for mixing.
[0012] Preferably, the particle size of the PEEK used is 50-75 μm, the particle size of the boron nitride used is 1-25 μm, and the particle size of the polytetrafluoroethylene used is 5-15 μm.
[0013] Preferably, the sphericity of the powders of PEEK, boron nitride, and polytetrafluoroethylene is ≥0.8.
[0014] Preferably, the boron nitride is hexagonal boron nitride.
[0015] Preferably, the specific surface pattern structure includes one or more of hills, grooves, and spiral textures.
[0016] Preferably, the preheating temperature of the powder bed used in the laser powder bed melting process is 325-335°C, and the thickness of the pre-laid powder bed is 5mm.
[0017] Preferably, the powder feeding temperature during the laser powder bed melting process is 260-280℃, the laser power is 35-38W, the scanning speed is 2000-2800mm / s, the layer thickness is 0.1mm, and the scanning interval is 0.1mm.
[0018] Preferably, during the laser powder bed melting process, the powder bed after printing is further spread with powder to a thickness of 3 mm, and then subjected to heat preservation annealing treatment at a temperature of 290-310°C for 1.5-2 hours.
[0019] The present invention also discloses a PEEK-based self-lubricating composite material part prepared by the above-described molding method.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The molding method for PEEK-based self-lubricating composite parts disclosed in this invention uses boron nitride and polytetrafluoroethylene (PTFE) as reinforcing materials. One advantage lies in the material selection, primarily including: 1) Boron nitride is an excellent solid lubricant, especially h-BN. Its atomic layers are connected by weak van der Waals forces, making hexagonal boron nitride easily shear to form slip surfaces, significantly reducing the coefficient of friction. The addition of h-BN also improves the wear resistance of the composite material. h-BN has excellent thermal stability, allowing PEEK to maintain its lubricating properties in high-temperature environments. h-BN can enhance the thermal conductivity of PEEK, facilitating rapid heat transfer; 2) Polytetrafluoroethylene (PTFE) has good dispersibility, further reducing the coefficient of friction and providing continuous lubrication, also contributing to improved wear resistance of PEEK. PTFE can reduce adhesion between PEEK and other materials; 3) The combination of h-BN and PTFE can produce a synergistic effect, forming a more uniform and powerful lubricating layer, further improving the self-lubricating performance of PEEK. Due to the thermal stability of h-BN and PTFE, PEEK can operate over a wider temperature range. In addition to lubrication properties, the addition of h-BN and PTFE effectively reduces warpage during laser powder bed melting, improving the mechanical properties of PEEK-based composites.
[0022] On the other hand, from the perspective of forming process, laser powder bed melting (LPBF) has the following three advantages: 1) LPBF technology allows the manufacture of parts with complex geometries and internal structures, which is difficult to achieve in traditional manufacturing methods; 2) LPBF technology can achieve micron-level resolution, which means that predetermined microtextures or patterns can be created on the surface of parts, realizing macro-micro integrated forming, thereby improving lubrication performance and other functional properties; 3) LPBF technology allows the use of a variety of different types of materials, facilitating the exploration of the forming performance of modified materials; 4) Compared with traditional subtractive processing methods, laser powder bed melting technology can minimize waste generation, helping to reduce resource waste and lower costs.
[0023] Therefore, by utilizing the method for preparing and forming self-lubricating composite materials with improved tribological properties provided by this invention, composite material parts with arbitrarily complex shapes and structures can be manufactured, possessing excellent self-lubricating properties and suitable for environments such as vacuum and high temperature where lubricating oils and greases are unstable or unsuitable.
[0024] Furthermore, the forming method of the present invention employs surface patterning technology, which has the following advantages:
[0025] 1) The pattern structure designed in this invention, which combines "hill" shapes, grooves, "earthworm"-like protrusions, and spiral textures, allows the grooves to act as reservoirs for solid lubricants. During friction, these patterns gradually release lubricant, providing continuous lubrication. When the lubricant is consumed or removed from the contact area, these patterns can refill by absorbing surrounding lubricant; 2) The hill-shaped and spiral protrusion pattern structure reduces the actual contact area between two contact surfaces, thereby reducing friction. When used in conjunction with a solid lubricant, this reduced contact area can further reduce the coefficient of friction; 3) These surface patterns can trap debris generated during wear, preventing it from further participating in friction and reducing wear. In some applications, the surface pattern can store not only solid lubricants but also liquid lubricants, such as oil or water, providing mixed lubrication; 4) These surface patterns help disperse heat generated during friction, reducing the temperature of the contact area. The solid lubricant can further help manage this heat, providing more stable lubrication conditions and helping to distribute the solid lubricant evenly within the contact area, ensuring effective lubrication throughout the entire contact area.
[0026] Furthermore, maintaining the powder feeding temperature at 260–280°C during the printing process has the following two advantages: 1) Increasing the powder feeding temperature to be close to the processing temperature can improve the temperature uniformity of the powder bed after powder spreading and reduce warping; 2) Appropriately increasing the powder feeding temperature can improve the sphericity of the powder, thereby improving the powder flowability and aiding in forming.
[0027] Furthermore, after printing, a heat preservation annealing treatment is adopted, which is equivalent to slowly cold crystallizing the formed part in a range below the melting temperature and above the glass transition temperature, thereby improving the Z-direction tensile strength of the formed part to a certain extent.
[0028] The PEEK-based self-lubricating composite material parts prepared by the molding method provided by this invention have advantages such as high precision, excellent self-lubricating properties, mechanical properties, wear resistance, chemical stability, and thermal conductivity. Attached Figure Description
[0029] Figure 1 A process flowchart for the molding method of PEEK-based self-lubricating composite material parts provided by the present invention;
[0030] Figure 2 This is a process flow diagram of a molding method for a PEEK-based self-lubricating composite material part provided by a specific embodiment of the present invention;
[0031] Figure 3 This is a schematic diagram of the microstructure of the surface of the friction and wear test specimen in Embodiment 1 of the present invention;
[0032] Figure 4 This is a schematic diagram of the microstructure of the surface of the friction and wear test specimen in Embodiment 2 of the present invention;
[0033] Figure 5 This is a schematic diagram of the microscopic pattern on the surface of the friction and wear test specimen in Embodiment 3 of the present invention. Detailed Implementation
[0034] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0035] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0036] See Figure 1 A method for forming a PEEK-based self-lubricating composite material part, comprising:
[0037] S1: PEEK, boron nitride and polytetrafluoroethylene are mixed to obtain PEEK-based self-lubricating composite powder;
[0038] S2: Design a specific surface pattern structure in advance in the CAD model, and use computer-aided design software to make the size and distribution of the pattern meet the specific application requirements to obtain the part model;
[0039] S3: Based on the part model, PEEK-based self-lubricating composite material powder is printed using LPBF macro-micro integrated printing technology to obtain PEEK-based self-lubricating composite material parts with specific surface patterns.
[0040] See Figure 2 The present invention provides a method for forming a PEEK self-lubricating composite material with improved tribological properties, comprising the following steps:
[0041] 1) Polyetheretherketone (PEEK), boron nitride (BN), and polytetrafluoroethylene (PTFE) are dried separately and then thoroughly mixed. The drying temperature is 120–150°C, and the drying time is 600–720 min. A planetary mixer can be used for mixing. After mixing, a PEEK-based self-lubricating composite material is obtained. The particle size of PEEK is 50–75 μm, the particle size of boron nitride is 1–25 μm, and the particle size of PTFE is 5–15 μm. The sphericity of the powders is ≥0.8. Based on the total mass of the PEEK-based self-lubricating composite material powder, the content of PEEK is 75%–80%, the content of boron nitride is 10%–15%, and the content of PTFE is 10%–15%. More preferably, the content of PEEK is 80%, the content of boron nitride is 10%, and the content of PTFE is 10%.
[0042] 2) Specific surface patterns are pre-designed in the CAD model. The surface patterns designed in this invention are micro-pattern structures composed of combinations of "hills", grooves, spiral textures, etc. Computer-aided design software is used to ensure that the size and distribution of the patterns meet specific application requirements, resulting in an optimized part model.
[0043] Specifically, microscopic patterns are designed on the surface of the model to be subjected to friction using 3D modeling software such as SolidWorks, UG, and PROE. Micron-level pattern units, such as hills and grooves, are arrayed on the model surface to ensure that application requirements are met. After the design is completed, the overall model is saved as an STL file, which is then imported into slicing software such as Autodesk Netfabb Ultimate for slicing. Finally, the sliced file is imported into the printing software of the LPBF equipment for printing.
[0044] 3) Import the optimized part model data from step 2) into a laser powder bed fusion (LPBF) forming machine. By adjusting the laser spot size, perform LPBF macro-micro integrated forming on the self-lubricating composite material prepared in S1 to obtain a preliminary part of the PEEK-based self-lubricating composite material. During the printing process, the preheating temperature of the powder bed is 325-335℃, the pre-laid powder bed thickness is 5mm, the powder feeding temperature is 260-280℃, the laser power is 35-38W, the scanning speed is 2000-2800mm / s, the layer thickness is 0.1mm, and the scanning interval is 0.1mm.
[0045] 4) After step 3) is completed, continue to spread powder on the powder bed to a thickness of 3 mm, and then perform heat preservation annealing treatment at a temperature of 290-310℃ for 1.5-2 hours.
[0046] 5) After annealing, turn off the heating device and allow the part to cool naturally. Finally, remove the part and clean the powder to obtain the PEEK-based self-lubricating composite material part.
[0047] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments:
[0048] Example 1
[0049] A method for forming a PEEK-based self-lubricating composite material part includes the following steps:
[0050] 1) Polyether ether ketone with a particle size of 50-75 μm, hexagonal boron nitride with a particle size of 1-25 μm, and polytetrafluoroethylene with a particle size of 5-15 μm were dried separately at a drying temperature of 120-150℃ for 600-720 min. Then, they were thoroughly mixed in a mass ratio of 8:1:1 to obtain a PEEK-based self-lubricating composite material. The sphericity of the powders was ≥0.8.
[0051] 2) The required surface pattern is pre-designed in the CAD model. In this embodiment, the surface of the test model is designed as a micro-pattern structure consisting of a combination of "hills" and pits. Figure 3 Computer-aided design software is used to ensure that the size and distribution of the pattern meet specific application requirements, resulting in an optimized part model.
[0052] 3) Import the optimized part model data from step 2) into a laser powder bed fusion (LPBF) forming machine, and use the PEEK-based self-lubricating composite material prepared in step 1) to perform LPBF macro-micro integrated forming to obtain a preliminary part of the PEEK-based self-lubricating composite material. During the printing process, the preheating temperature of the powder bed is 325-335℃, the pre-laid powder bed thickness is 5mm, the powder feeding temperature is 260-280℃, the laser power is 35-37W, the scanning speed is 2500-2800mm / s, the layer thickness is 0.1mm, and the scanning spacing is 0.1mm.
[0053] 4) After step 3) is completed, continue to spread powder on the powder bed to a thickness of 3 mm, and then perform heat preservation annealing treatment at a temperature of 290-310℃ for 1.5-2 hours.
[0054] 5) After annealing, turn off the heating device and allow the part to cool naturally. Finally, remove the part and clean the powder to obtain the PEEK-based self-lubricating composite material part.
[0055] Example 2
[0056] A method for forming a PEEK-based self-lubricating composite material part includes the following steps:
[0057] 1) Polyether ether ketone with a particle size of 50-75 μm, hexagonal boron nitride with a particle size of 1-25 μm, and polytetrafluoroethylene with a particle size of 5-15 μm were dried separately at a drying temperature of 120-150℃ for 600-720 min. Then, they were thoroughly mixed in a mass ratio of 8:1:1 to obtain a PEEK-based self-lubricating composite material. The sphericity of the powders was ≥0.8.
[0058] 2) The required surface pattern is pre-designed in the CAD model. In this embodiment, the surface of the test model is designed as a micro-pattern structure consisting of a combination of "earthworm"-like protrusions and grooves. Figure 4 Computer-aided design software is used to ensure that the size and distribution of the pattern meet specific application requirements, resulting in an optimized part model.
[0059] 3) Import the optimized part model data from step 2) into a laser powder bed fusion (LPBF) forming machine, and use the PEEK-based self-lubricating composite material prepared in step 1) to perform LPBF macro-micro integrated forming to obtain a preliminary part of the PEEK-based self-lubricating composite material. During the printing process, the preheating temperature of the powder bed is 325-335℃, the pre-laid powder bed thickness is 5mm, the powder feeding temperature is 260-280℃, the laser power is 35-37W, the scanning speed is 2500-2800mm / s, the layer thickness is 0.1mm, and the scanning spacing is 0.1mm.
[0060] 4) After step 3) is completed, continue to spread powder on the powder bed to a thickness of 3 mm, and then perform heat preservation annealing treatment at a temperature of 290-310℃ for 1.5-2 hours.
[0061] 5) After annealing, turn off the heating device and allow the part to cool naturally. Finally, remove the part and clean the powder to obtain the PEEK-based self-lubricating composite material part.
[0062] Example 3
[0063] A method for forming a PEEK-based self-lubricating composite material part includes the following steps:
[0064] 1) Polyether ether ketone with a particle size of 50-75 μm, hexagonal boron nitride with a particle size of 1-25 μm, and polytetrafluoroethylene with a particle size of 5-15 μm were dried separately at a drying temperature of 120-150℃ for 600-720 min. Then, they were thoroughly mixed in a mass ratio of 8:1:1 to obtain a PEEK-based self-lubricating composite material. The sphericity of the powders was ≥0.8.
[0065] 2) The required surface pattern is pre-designed in the CAD model. In this embodiment, the surface of the test model is designed as a micro-pattern structure with a combination of spiral textures. Figure 5 Computer-aided design software is used to ensure that the size and distribution of the pattern meet specific application requirements, resulting in an optimized part model.
[0066] 3) Import the optimized part model data from step 2) into a laser powder bed fusion (LPBF) forming machine, and use the PEEK-based self-lubricating composite material prepared in step 1) to perform LPBF macro-micro integrated forming to obtain a preliminary part of the PEEK-based self-lubricating composite material. During the printing process, the preheating temperature of the powder bed is 325-335℃, the pre-laid powder bed thickness is 5mm, the powder feeding temperature is 260-280℃, the laser power is 35-37W, the scanning speed is 2500-2800mm / s, the layer thickness is 0.1mm, and the scanning spacing is 0.1mm.
[0067] 4) After step 3) is completed, continue to spread powder on the powder bed to a thickness of 3 mm, and then perform heat preservation annealing treatment at a temperature of 290-310℃ for 1.5-2 hours.
[0068] 5) After annealing, turn off the heating device and allow the part to cool naturally. Finally, remove the part and clean the powder to obtain the PEEK-based self-lubricating composite material part.
[0069] Comparative Example
[0070] The process of manufacturing pure PEEK material parts using conventional laser powder bed fusion molding technology includes the following steps:
[0071] 1) Dry polyether ether ketone powder with a sphericity ≥ 0.8 and a particle size of 50-75 μm at a drying temperature of 120-150℃ for 600-720 min.
[0072] 2) Import the part model data, which is the same as in Example 1 but without surface patterning, into the laser powder bed fusion (LPBF) forming machine. Use the pure PEEK material prepared in step 1) to perform LPBF macro-micro integrated forming to obtain a preliminary part made of pure PEEK material. During the printing process, the preheating temperature of the powder bed is 325-335℃, the pre-laid powder bed thickness is 5mm, the laser power is 27-29W, the scanning speed is 1500-2000mm / s, the layer thickness is 0.1mm, and the scanning spacing is 0.1mm.
[0073] 3) After printing, allow the part to cool naturally, then remove the part and clean the powder to obtain a pure PEEK material part.
[0074] Friction and wear performance test: The parts obtained in the above examples and comparative examples were subjected to friction and wear performance tests. The test results are shown in Table 1.
[0075] Table 1. Test results of friction and wear performance of the parts in the examples and comparative examples.
[0076] Test methods ASTM G99-04 - Example 1 0.046 4.99 Example 2 0.051 5.32 Example 3 0.053 4.46 Comparative Example 0.08 5.89
[0077] As shown in Table 1, the PEEK-based self-lubricating composite material obtained by adding hexagonal boron nitride and polytetrafluoroethylene, after different surface patterning treatments and laser powder bed melting optimization processes, has a lower coefficient of friction and wear rate than the parts obtained by ordinary laser powder bed melting forming of pure PEEK material. This significantly improves its friction and wear performance. Parts manufactured by this material and forming method can be used in vacuum and high-temperature environments where lubricating oil or grease is not suitable, and has broad market potential and significant engineering application value.
[0078] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A molding method for a PEEK-based self-lubricating composite material part, characterized in that, include: PEEK, boron nitride and polytetrafluoroethylene were mixed to obtain PEEK-based self-lubricating composite powder; A specific surface pattern structure is pre-designed in the CAD model, and computer-aided design software is used to make the size and distribution of the pattern meet the specific application requirements to obtain the part model; the specific surface pattern structure includes one or more of hills, grooves and spiral textures. Based on the part model, PEEK-based self-lubricating composite material powder was printed using LPBF macro-micro integrated printing technology to obtain PEEK-based self-lubricating composite material parts with specific surface patterns. The preheating temperature of the powder bed used in the laser powder bed melting process is 325~335℃, the pre-lay powder bed thickness is 5mm, the powder feeding temperature during the laser powder bed melting process is 260~280℃, and the powder bed after printing is further laid with powder during the laser powder bed melting process, with a powder layer thickness of 3mm, and then heat preservation annealing treatment is performed, with a heat preservation temperature of 290~310℃ and a heat preservation time of 1.5~2 hours.
2. The molding method for PEEK-based self-lubricating composite material parts according to claim 1, characterized in that, In the PEEK-based self-lubricating composite powder, PEEK accounts for 75%~80% by mass, boron nitride accounts for 10%~15%, and polytetrafluoroethylene accounts for 10%~15%. During preparation, PEEK, boron nitride, and polytetrafluoroethylene are dried separately and then mixed. The drying temperature is 120~150℃ and the drying time is 600~720 min. A planetary stirrer is used for mixing.
3. The molding method for PEEK-based self-lubricating composite material parts according to claim 1, characterized in that, The particle size of the PEEK used is 50~75μm, the particle size of the boron nitride used is 1~25μm, and the particle size of the polytetrafluoroethylene used is 5~15μm.
4. The molding method for PEEK-based self-lubricating composite material parts according to claim 1, characterized in that, The sphericity of PEEK, boron nitride, and polytetrafluoroethylene powders is ≥0.
8.
5. The molding method for PEEK-based self-lubricating composite material parts according to claim 1, characterized in that, Hexagonal boron nitride is used for boron nitride.
6. The molding method for a PEEK-based self-lubricating composite material part according to claim 1, characterized in that, The laser power is 35~38 W, the scanning speed is 2000~2800 mm / s, the layer thickness is 0.1 mm, and the scanning spacing is 0.1 mm.
7. A PEEK-based self-lubricating composite material part prepared by the molding method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Solid lubrication treatment method for friction pair laser micro-texture surface
CN105782243A
Polyether-ether-ketone-based polymer alloy composite material, and preparation method and application thereof
CN111269530A
Preparation method of PEEK composite wire for 3D printer
CN113956610A